2003
DOI: 10.1074/jbc.m309122200
|View full text |Cite
|
Sign up to set email alerts
|

PINCH-1 Is an Obligate Partner of Integrin-linked Kinase (ILK) Functioning in Cell Shape Modulation, Motility, and Survival

Abstract: PINCH-1 is a widely expressed focal adhesion protein that forms a ternary complex with integrin-linked kinase (ILK) and CH-ILKBP/actopaxin/␣-parvin (abbreviated as ␣-parvin herein). We have used RNA interference, a powerful approach of reverse genetics, to investigate the functions of PINCH-1 and ILK in human cells. We report here the following.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
242
3
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(280 citation statements)
references
References 58 publications
27
242
3
8
Order By: Relevance
“…Notably, we have observed that RSU1 is consistently downregulated in prostate cancer 3,24,26 , further suggesting a tumor suppressor role for this gene; however, to date, the mechanism by which RSU1 exerts its effects has not been elucidated. Here our model predicted, and we experimentally confirmed that RSU1 interacts with LIMS1, an adaptor protein involved in integrin signaling at focal adhesions 31 . Furthermore, we found that when RSU1 was expressed alone, it had diffuse cytoplasmic localization, but when it was coexpressed with LIMS1, it had discrete punctate cytoplasmic localization (Fig.…”
Section: A N a Ly S I Ssupporting
confidence: 76%
“…Notably, we have observed that RSU1 is consistently downregulated in prostate cancer 3,24,26 , further suggesting a tumor suppressor role for this gene; however, to date, the mechanism by which RSU1 exerts its effects has not been elucidated. Here our model predicted, and we experimentally confirmed that RSU1 interacts with LIMS1, an adaptor protein involved in integrin signaling at focal adhesions 31 . Furthermore, we found that when RSU1 was expressed alone, it had diffuse cytoplasmic localization, but when it was coexpressed with LIMS1, it had discrete punctate cytoplasmic localization (Fig.…”
Section: A N a Ly S I Ssupporting
confidence: 76%
“…Consistently, several lines of evidence have implicated PINCH1/2 as suppressors of apoptosis. For example, in vitro inhibition of PINCH1 expression in HeLa cervical, fibrosarcoma, breast, prostate, hepatocellular, lung, and colon carcinomas leads to apoptosis 109,112 . In vivo, knockout of PINCH1 in embryonic neural crest cells caused enhanced apoptosis 113 .…”
Section: The Ipp Complex (Ilk/pinch and Parvin) And Cancer Biologymentioning
confidence: 99%
“…In cell culture, reductions in both ILK and PINCH protein levels are observed when either ILK or PINCH levels are depleted either by RNA interference or targeted gene disruption (Fukuda et al, 2003;Xu et al, 2005;Stanchi et al, 2009). A recent publication has also demonstrated mutual stabilization of PINCH and ILK in vivo using antisense morpholinos in zebrafish (Meder et al, 2011).…”
Section: Ilk-pinch-rsu-1 Adhesion Complexes 3187mentioning
confidence: 99%
“…First, the N-terminal LIM domain of PINCH interacts directly with the Nterminal ankyrin repeat domain (ANKR) of ILK Tu et al, 1999). Second, depletion of either ILK or PINCH results in reduction in the levels of the other, indicating a mutual stabilization of these two proteins (Fukuda et al, 2003;Stanchi et al, 2009;Meder et al, 2011). Third, targeted disruption of the interaction between PINCH and ILK in mammalian cell culture experiments by a point mutation in LIM1 of PINCH results in disturbances in cell spreading and survival, as well as reduced stability of both PINCH and ILK (Velyvis et al, 2001;Zhang et al, 2002;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%